Exhaled nitric oxide and asthma: complex interactions between atopy, airway responsiveness, and symptoms in a community population of children. Issue 12 (26th November 2003) - Franklin, P J; Turner, S W; Le Souëf, P N; Stick, S M
Abstract : Background: Exhaled nitric oxide (FENO ) is raised in asthmatic children, but there are inconsistencies in the relationship between FENO and characteristics of asthma, including atopy, increased airway responsiveness (AR), and airway inflammation. The aim of this study was to investigate the relationship between FENO and asthma, atopy, and increased AR in children. Methods: One hundred and fifty five children (79 boys) of mean age 11.5 years underwent an assessment that included FENO measurements, spirometric tests, inhaled histamine challenge, and a skin prick test. Blood was collected for eosinophil count. Current and past asthma like symptoms were determined by questionnaire. Results: In multiple linear regression analyses FENO was associated with atopy (p<0.001), level of AR (p = 0.005), blood eosinophil count (p = 0.007), and height (p = 0.002) but not with physician diagnosed asthma (p = 0.1) or reported wheeze in the last 12 months (p = 0.5). Separate regression models were conducted for atopic and non-atopic children and associations between FENO and AR, blood eosinophils and height were only evident in atopic children. Exhaled NO was raised in children with a combination of atopy and increased AR independent of symptoms. Conclusion: Raised FENO seems to be associated with an underlying mechanism linking atopy and AR but not necessarily respiratory symptoms.